METODE, CORAK DAN PENDEKATAN MUKTAZILAH DALAM PENAFSIRAN AL-QUR’AN - Ahmad Zabidi (Institut Agama Islam Sultan Muhammaad Syafiuddin Sambas, 2020)
The history of the interpretation of the Koran has gone through various long, complicated and complex phases. Initially, exegesis was an attempt to find an appropriate meaning in accordance with the text, but at a later stage the projection of interpretation was contaminated with attempts to subdue the Koran for the benefit of religious groups and individuals. Historically, differences in views among Muslims have occurred since the beginning of Islam itself. That means when the Apostle was still alive, differences in views had appeared, the Apostle himself could still reconcile therapy. However, since the Prophet died, differences have emerged and are difficult to control. This difference is not only in terms of adhering to the sunnah or not, but also includes other matters such as fiqh and aqidah, including the interpretation of the Koran. The emergence of these differences cannot be separated from the differences that occurred between the reality of the era of the Prophet and the era after him. The need to interpret sacred texts is of greater urgency. That is one of the driving forces for the emergence of interpreters as messengers of God to provide benefits for the people. The appearance of these interpreters on the one hand is able to provide guidance for the Ummah, but on the other hand it also brings people unrest. Not a few things happened slander, ignorance, torture and so on due to different interpretations. Fanaticism towards groups with certain interpretations that are believed to be correct is increasingly rampant. So that there emerged schools in various fields such as the kalam and fiqh schools, which in essence all these schools were closely related to interpretation. This means that in these schools there are roots of differences in the method or paradigm of interpreting the holy text. One of the schools that had triumphed in his time was Mu'tazilah. Mu'tazilah is a rationalist school that seems unique when it comes to methods and approaches in its interpretation. According to the author, this uniqueness lies in the ra'yi style which at that time was considered controversial. Despite reaping controversy, they continue to develop their thinking so that they produce works with their distinctive style.